Discussion of On the Association between Net Monetary Position and Equity Security Prices - Watts, Ross L. (Journal of Accounting Research, 1978)
Ross L. Watts, Discussion of On the Association between Net Monetary Position and Equity Security Prices, Journal of Accounting Research, Vol. 16, Studies on Changes in General and Specific Prices: Empirical Research and Public Policy Issues (1978), pp. 148-153